Factors influence real estate agents sales performance: in case of organizational controls and motivation plans - Fong, Jia Xun (2022)
Buying property involved many complex processes. Real estate agent as the intermediaries of the property market, function in deliver local market knowledge to bridge the information gap between buyers and sellers. Their job scope included administrative duties, lead generation, working with sellers and buyers, meetings and property viewing, and others. Since there are not centralize platform or market in the property industry, the information gathering is a hassle for property buyers. Here come to the important of estate agents to the market. Also there are numbers of previous studies said that the role and performance of intermediaries had great impact towards organization and market performance. If the estate agents have poor performance, it could bring a lot of difficulties to the buyers and also the market. In the current market, organization often use company key performance index (KPI) to measure the performance of their salesforce. Seldom looking from organizational perspective will reduce the reliability of the measurement. In this case, it is important to find out the factors influence estate agents’ sales performance in the case of organizational controls and motivation plans. The independent variables in this study are sales territory alignment, supervisory behavior, non- motivation plans and financial motivation plans. The dependent variable thus will be the estate agents’ sales performance. The study aims to determine the impact of organizational controls to real estate agents’ sales performance. And how the impact of motivation plans to the real estate agents’ sales performance. The methodology of the study is the online questionnaire survey of 100 real estate agents who mainly live and work at Selangor region. While for the data analysis, the statistical package social sciences (SPSS) was applied. The result of the study shows that all the independent variables have a positive influence on dependent variable. However, one of the variable had insignificant influence towards estate agents’ sales performance, which is the supervisory behaviour. This can be supported by Doug J. Chung (2015), who claimed that the salesperson who is under commission-based salary had lesser direct supervision by supervisors. Besides that, with the understanding how the factors influence estate agents’ sales performance, it can help the agencies, organizations and relevant department in Malaysia to enhance their salesforce sales performance. Furthermore, contribute to the current body of literature.